The mermaid's child - Baker, Jo (Vintage original, 2015)
"In this fantastical novel, the acclaimed author of Longbourn brings us the magical story of a young girl in search of her mother...who just might be a mermaid. Malin has always been different, and when her father dies, leaving her alone, her choice is clear: stay, and remain an outsider forever, or leave in search of the mythical inheritance she is certain awaits her. Apprenticed to a series of strange and wonderful characters, Malin embarks on a grueling journey that crosses oceans and continents--from the high seas to desert plains--and leads to a discovery that she could never have expected. Beautifully written and hauntingly strange, The Mermaid's Child is a remarkable piece of storytelling, and an utterly unique work of fantasy from literary star Jo Baker"--